Phase 1 study of CART-ddBCMA for the treatment of subjects with relapsed and refractory multiple myeloma - Frigault, Matthew J.; Bishop, Michael R.; Rosenblatt, Jacalyn; O’Donnell, Elizabeth K.; Raje, Noopur; Cook, Daniella; Yee, Andrew J.; Logan, Emma; Avigan, David E.; Jakubowiak, Andrzej; Shaw, Kit; Daley, Heather; et al. (Blood advances, 2023)
•CART-ddBCMAs are safe for use in patients with relapsed or refractory multiple myeloma.•CART-ddBCMAs produce deep and durable responses in patients with poor prognostic factors. [Display omitted] Relapsed and refractory multiple myeloma (RRMM) is a plasma cell neoplasm defined by progressively refractory disease necessitating chronic and increasingly intensive therapy. Despite recent advances, limited treatment options exist for RRMM. This single-arm, open label phase 1 study aimed to evaluate the safety of novel B-cell maturation antigen (BCMA)-targeting chimeric antigen receptor (CAR) T construct that leverages a completely synthetic antigen-binding domain (CART-ddBCMA), which was specifically engineered to reduce immunogenicity and improve CAR cell surface stability. Thirteen patients ≥18 years with RRMM who received at least 3 prior regimens of systemic therapy were enrolled in the study. Patients received a single dose of 100 × 106 CART-ddBCMA (DL1) or 300 × 106 CART-ddBCMA (DL2) following standard lymphodepleting chemotherapy. The primary endpoints of the study were to evaluate the incidence of treatment emergent adverse events, including dose-limiting toxicities, and establish a recommended phase 2 dose. Results showed that CART-ddBCMA was well tolerated and demonstrated a favorable toxicity profile. Only 1 case of grade ≥3 cytokine release syndrome and 1 case of immune effector cell–associated neurotoxicity were reported; both were at DL2 and were manageable with standard treatment. No atypical neurological toxicities and Parkinson disease-like movement disorders were observed. The maximum tolerated dose was not reached. All infused patients responded to CART-ddBCMA, and 9/12 (75%) patients achieved complete response/stringent complete response. Responses deepened over time, and at the time of last data-cut (median follow-up 56 weeks), 8/9 (89%) evaluable patients achieved minimal residual disease negativity. In conclusion, the findings demonstrate the safety of CART-ddBCMA cells and document durable responses to CART-ddBCMA in patients with RRMM. This trial was registered at www.clinicaltrials.gov as #NCT04155749.